Emerging roles of T helper 17 and regulatory T cells in lung cancer progression and metastasis. Issue 1 (December 2016) - Marshall, Erin; Ng, Kevin; Kung, Sonia; Conway, Emma; Martinez, Victor; Halvorsen, Elizabeth; Rowbotham, David; Vucic, Emily; Plumb, Adam; Becker-Santos, Daiana; Enfield, Katey; Kennett, Jennifer; et al.
Abstract Lung cancer is a leading cause of cancer-related deaths worldwide. Lung cancer risk factors, including smoking and exposure to environmental carcinogens, have been linked to chronic inflammation. An integral feature of inflammation is the activation, expansion and infiltration of diverse immune cell types, including CD4+ T cells. Within this T cell subset are immunosuppressive regulatory T (Treg) cells and pro-inflammatory T helper 17 (Th17) cells that act in a fine balance to regulate appropriate adaptive immune responses. In the context of lung cancer, evidence suggests that Tregs promote metastasis and metastatic tumor foci development. Additionally, Th17 cells have been shown to be an integral component of the inflammatory milieu in the tumor microenvironment, and potentially involved in promoting distinct lung tumor phenotypes. Studies have shown that the composition of Tregs and Th17 cells are altered in the tumor microenvironment, and that these two CD4+ T cell subsets play active roles in promoting lung cancer progression and metastasis. We review current knowledge on the influence of Treg and Th17 cells on lung cancer tumorigenesis, progression, metastasis and prognosis. Furthermore, we discuss the potential biological and clinical implications of the balance among Treg/Th17 cells in the context of the lung tumor microenvironment and highlight the potential prognostic function and relationship to metastasis in lung cancer.